Quality of knee osteoarthritis care in the Netherlands: a survey on the perspective of people with osteoarthritis - J. M. H. Oomen; Y. A. S. Peters; C. H. van den Ende; H. J. Schers; W. J. J. Assendelft; J. E. Vriezekolk; S. Koëter (BMC, 2022)
Abstract Background Quality indicators (QIs) are used to monitor quality of care and adherence to osteoarthritis (OA) standards of care. Patient reported QIs can identify the most important gaps in quality of care and the most vulnerable patient groups. The aim of this study was to capture the perspective of people with knee OA (KOA) in the Netherlands on the quality of care received, and explore determinants related to lower achievement rates. Methods We sent an online survey to all members of The Dutch Knee Panel (n = 622) of the Sint Maartenskliniek Nijmegen, the Netherlands between September and October 2019. The survey consisted of a slightly adapted version of the "OsteoArthritis Quality Indicator" (OA-QI) questionnaire (18 items; yes, no, N/A); a rating of quality of KOA care on a 10-point scale; a question on whether or not one wanted to see change in the care for KOA; and an open-ended question asking recommendations for improvement of OA care. Furthermore, sociodemographic and disease related characteristics were collected. Pass rates for separate QIs and pass rates on patient level were calculated by dividing the number of times the indicator was achieved by the number of eligible persons for that particular indicator. Results A total of 434 participants (70%) completed the survey. The mean (SD) pass rate (those answering "Yes") for separate QIs was 49% (20%); ranging from 15% for receiving referral for weight reduction to 75% for patient education on how to manage knee OA. The mean (SD) pass rate on patient level was 52% (23%). Presence of OA in other joints, comorbidities, and having a knee replacement were associated with higher pass rates. On average, a score of 6.5 (1.6) was given for the quality of care received, and the majority of respondents (59%) wanted change in the care for KOA. Of 231 recommendations made, most often mentioned were the need for tailoring of care (14%), more education (13%), and more empathy and support from healthcare providers (12%). Conclusion This study found patients are only moderately satisfied with the OA care received, and showed substantial gaps between perceived quality of care for OA and internationally accepted standards. Future research should focus on the underlying reasons and provide strategies to bridge these gaps.